2016
DOI: 10.3758/s13414-016-1210-8
|View full text |Cite
|
Sign up to set email alerts
|

Five shades of grey: Generalization in distractor-based retrieval of S-R episodes

Abstract: Binding theories assume that a stimulus and a response made to it are bound together, as in the case of the theory of event coding, in an event file (Hommel, Müsseler, Aschersleben, & Prinz, Behavioral and Brain Sciences, 24(05), 849-937, 2001). This binding occurs after even a single encounter with the stimulus and the response. Repeating any part of the event file will cause the entire file to be retrieved. However not only are relevant stimuli bound with responses but even irrelevant stimuli that co-occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 24 publications
6
43
0
Order By: Relevance
“…The characteristics of SR binding and learning processes appear to be similar (e.g., Giesen & Rothermund, 2014;Moeller & Frings, 2014;Singh, Moeller, & Frings, 2016). In line with this, what is known from sequence learning in sequential response time (SRT) tasks (see Abrahamse, Jiménez, Verwey, & Clegg, 2010, for a review) seems to be mirrored in the present results.…”
Section: Discussionsupporting
confidence: 84%
“…The characteristics of SR binding and learning processes appear to be similar (e.g., Giesen & Rothermund, 2014;Moeller & Frings, 2014;Singh, Moeller, & Frings, 2016). In line with this, what is known from sequence learning in sequential response time (SRT) tasks (see Abrahamse, Jiménez, Verwey, & Clegg, 2010, for a review) seems to be mirrored in the present results.…”
Section: Discussionsupporting
confidence: 84%
“…For each distractor condition a DRB effect was calculated as (RRDC-RRDR)-(RCDC-RCDR) for reaction times and error rates, while using the largest lightness value difference as the distractor change condition for all four distractor repetition conditions with exact repetition and decreasing similarity as the repetition conditions. In line with the generalization processes observed in Pavlovian conditioning (Pearce, 1987), the DRB effect was largest for the exact distractor repetition condition and decreased with increasing distractor dissimilarity; that is, Singh et al (2016) observed generalization processes in distractor-based retrieval (see Fig. 2A for the original data).…”
Section: Introductionsupporting
confidence: 72%
“…Thus, upon a subsequent presentation of the distractor, the (associated) response to the target is executed. With these thoughts in mind, Singh, Moeller, and Frings (2016) hypothesized that processes that impact Pavlovian conditioning should also impact DRB effects: Because in Pavlovian conditioning generalization takes place, that is, conditioned responses can occur in situations that are similar, but not exactly the same as those situations they were learned in (Pearce, 1987), generalization might take place in distractor-based retrieval as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the reduced influence of the distractor stimulus might reflect a perceptual mismatch between the prime and probe in the appearance of the distractor stimulus, rather than the impact of a context change. However, the literature suggests that perceptually similar distractors (Singh, Moeller, & Frings, 2016), or even only conceptually similar distractor repetitions (Frings, Moeller, & Rothermund, 2013), elicit distractor-based retrieval. Here, perceptually very similar distractor stimuli (dark vs. light bluish distractors of the same identity) elicited no retrieval in the context-shift conditions.…”
Section: Discussionmentioning
confidence: 99%